Estimating and Predicting Financial Series by Entropy-Based Inferential Model - Tanarat Rattanadamrongaksorn (2018)
© 2018, Springer International Publishing AG, part of Springer Nature. In this study, the non-parametric Inferential Model or IM with the entropy-based random set has been proposed for the investigation of financial data in the two statistical domains i.e. estimation and prediction. The samples from five financial markets were chosen for representing the different types of financial assets to make a conclusion about this new framework. We found that the Inferential Model performed equally well compared with the traditional method but was more robust so that it might be more appropriate for some specific uses.